Analyzing the Effectiveness of Marketing Sasak Handwoven Crafts through Immersive Metaverse Media - Baiq Handayani Rinuastuti; Abdurrahman; Regania Pasca Rassy (Journal of Economics and Management, 2026)
This study explores the potential of Metaverse-based marketing in promoting Tenun Sasak, a traditional handwoven textile that represents the cultural identity of Lombok, Indonesia. Using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) as the analytical framework, the study evaluates how several technology acceptance factors influence consumers’ intention to purchase Tenun Sasak after experiencing the product through a virtual reality gallery developed by the researchers. The examined factors include performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habit. A quantitative explanatory research design was applied, involving 100 respondents selected through purposive sampling. The collected data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that purchase intention is significantly influenced by performance expectancy (β = 0.19, p = 0.001), effort expectancy (β = 0.16, p = 0.009), hedonic motivation (β = 0.21, p < 0.001), price value (β = 0.14, p = 0.011), and habit (β = 0.18, p = 0.002). Meanwhile, social influence and facilitating conditions do not demonstrate significant effects. These results suggest that consumers are more likely to develop purchase intentions when Metaverse-based product experiences are perceived as beneficial, accessible, enjoyable, reasonably valuable, and aligned with their existing digital behavior. The findings highlight the relevance of immersive technology as an alternative marketing approach for traditional cultural products.